Intramolecular asymmetric oxidopyrylium-based [5 + 2] cycloadditions. Issue 41 (8th October 2020) - Rokey, Samantha N.; Simanis, Justin A.; Law, Chunyin M.; Pohani, Shilpa; Willens Behrends, Samantha; Bulandr, Jacob J.; Ferrence, Gregory M.; Goodell, John R.; Andrew Mitchell, T.
Graphical abstract: Highlights: Chiral auxiliary-based oxidopyrylium-based [5 + 2] cycloadditions investigated. Acetoxypyranones and silyloxypyrones were employed. Sulfinimines, oxazolidinones, hydrazones, and chiral enamines explored. Chiral enamines afforded excellent diastereoselectivity. Abstract: Intramolecular oxidopyrylium-based [5 + 2] cycloadditions utilizing chiral auxiliaries were investigated. Both acetoxypyranones and silyloxypyrones were employed and sulfinimines, oxazolidinones, hydrazones, and chiral enamines were explored. Carbonyl-based auxiliaries gave low selectivity, but enamines afforded excellent diastereoselectivity. Overall, facial selectivity varied significantly providing insight regarding the scope and limitation of chiral auxiliary-based oxidopyrylium-alkene [5 + 2] cycloadditions.